Innate lymphoid type 2 cells sustain visceral adipose tissue eosinophils and alternatively activated macrophages - Molofsky, Ari B. (The Rockefeller University Press, 2013)
Eosinophils in visceral adipose tissue (VAT) have been implicated in metabolic homeostasis and the maintenance of alternatively activated macrophages (AAMs). The absence of eosinophils can lead to adiposity and systemic insulin resistance in experimental animals, but what maintains eosinophils in adipose tissue is unknown. We show that interleukin-5 (IL-5) deficiency profoundly impairs VAT eosinophil accumulation and results in increased adiposity and insulin resistance when animals are placed on a high-fat diet. Innate lymphoid type 2 cells (ILC2s) are resident in VAT and are the major source of IL-5 and IL-13, which promote the accumulation of eosinophils and AAM. Deletion of ILC2s causes significant reductions in VAT eosinophils and AAMs, and also impairs the expansion of VAT eosinophils after infection with Nippostrongylus brasiliensis, an intestinal parasite associated with increased adipose ILC2 cytokine production and enhanced insulin sensitivity. Further, IL-33, a cytokine previously shown to promote cytokine production by ILC2s, leads to rapid ILC2-dependent increases in VAT eosinophils and AAMs. Thus, ILC2s are resident in VAT and promote eosinophils and AAM implicated in metabolic homeostasis, and this axis is enhanced during Th2-associated immune stimulation.